Looking through the keyhole: A case report of odontome with keyhole pattern in histopathology - Vaddadi Krishna Mohan; Sudha Gunasekaran; V S Aruna Jeslyn; Aysha Nabeela; B Barath; Bargavi Venkatesalu; Lekshmy Jayan (Wolters Kluwer Medknow Publications, 2020)
Odontome is the most frequent mixed type of odontogenic tumor comprising 22% of all odontogenic tumors. They are divided into two types namely, compound and complex types on the basis of the differentiation and organization of the dental tissues. The diagnosis of odontome relies on the clinical and radiographic evaluation of the lesion. This article presents an unusual case of compound composite odontome with prominent keyhole pattern in maxilla of a 23-year-old male patient.